A guide to collecting samples for flower and fruit developmental studies - Julius Jeiter; Erik Smets (Ecological Solutions and Evidence)
Abstract Developmental studies of flowers and fruits provide important data for evolutionary studies of flowering plants. Collecting the right samples is therefore crucial. For appropriate sampling, we distinguish between early, mid and late developmental stages, followed by anthesis, fruit developmental stages and fruit maturity. Sampling is preferably carried out in the field, but botanical gardens are also very important for sampling, always taking into account local regulations and legislation. Herbaria and alcohol collections in natural history institutions can also be consulted for material or stages that are difficult to obtain. Practical implications. We provide a list of equipment and materials required for collecting and storing, including details of fixatives. Finally, we also include some useful tips on how to collect the relevant samples for developmental and comparative morphological studies.